Cu/Pd cooperatively catalyzed tandem intramolecular anti-Markovnikov hydroarylation of unsaturated amides: facile construction of 3, 4-dihydroquinolinones via borylation/intramolecular C(sp3)–C(sp2) cross coupling. Issue 1 (1st December 2017) - Kuang, Zhijie; Li, Bingnan; Song, Qiuling
Abstract : An anti-Markovnikov hydroarylation of unsaturated amides via a Cu/Pd synergistically catalyzed cascade borylation/intramolecular sp 2 –sp 3 cross coupling has been disclosed. Abstract : An anti-Markovnikov hydroarylation of unsaturated amides via a Cu/Pd synergistically catalyzed cascade borylation/intramolecular sp 2 –sp 3 cross-coupling has been disclosed. 3, 4-Dihydroquinolinones, one type of important scaffold prevailing in pharmaceuticals and biologically active compounds, could be readily accessible with high regio-selectivity and high yields.